Class Management in the Indonesian Language Learning Process for Class V Students at State Primary School 3 Midang Gunungsari West Lombok - Zarwtun, Laela (International Journal of Sustainability in Research, 2023)
Teachers in their role as class managers in learning activities are required to have the abilities and skills so that the expected goals in managing learning activities can be achieved. This is because classroom management in learning activities is an effort made by teachers to create, maintain and develop learning motivation to achieve predetermined goals. Meanwhile, learning itself is the ability to manage operationally and efficiently components related to learning, to produce added value to these components by applicable norms/standards. Classroom management in the learning process which is emphasized in this study is the Indonesian language learning process in Class V of Midang Gunungsari 3 Elementary School, West Lombok with the Big Column (KB) and Big Circle (LB) student seating formations, as well as the obstacles faced by teachers. The results show that when the Indonesian language teacher implements classroom management in the learning process with students sitting in Large Columns (KB) and Large Circles, student learning outcomes average 7.6 grades higher than the Minimum Completeness Criteria (KKM) score for Indonesian Language subjects ( 7.5), while the obstacles faced by teachers when implementing classroom management in the learning process by implementing student seating formations, both Large Columns (KB) and Large Circles (LB), originate from teachers and students, who then seek solutions that originate from teachers. Meanwhile, it came from students, 3 students whose learning results were below the KKM score because they did not concentrate when taking part in the lesson and because they often did not go to school, namely through a special approach both when learning took place in the classroom and outside the classroom.